1966
DOI: 10.1029/wr002i002p00167
|View full text |Cite
|
Sign up to set email alerts
|

Recreation benefits from water pollution control

Abstract: A methodology for estimating direct recreational benefits from water pollution control was developed through a model of biological and behavioral relationships involved in sports angling. A biological production function was envisaged between inputs of angling effort and the output, or yield, of fish taken. The marginal product, angling success per unit of effort, was taken to represent the 'quality' of the recreational experience. Water pollution would cause deteriorations in dissolved oxygen, temperature, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…In these studies, the physical water quality indicators are found to significantly impact recreation demand, but because of the limited nature of the measures themselves, provide only a partial picture of value associated with possible water quality improvements. Other papers that have used one or more measures of water quality include von Haefen (2003), Atasoy, Palmquist and Phaneuf (2006), Phaneuf (2002), Kaoru, Smith, and Liu (1995), Ribaudo and Piper (1991), Russell and Vaughan (1982), and Stevens (1966).…”
mentioning
confidence: 98%
“…In these studies, the physical water quality indicators are found to significantly impact recreation demand, but because of the limited nature of the measures themselves, provide only a partial picture of value associated with possible water quality improvements. Other papers that have used one or more measures of water quality include von Haefen (2003), Atasoy, Palmquist and Phaneuf (2006), Phaneuf (2002), Kaoru, Smith, and Liu (1995), Ribaudo and Piper (1991), Russell and Vaughan (1982), and Stevens (1966).…”
mentioning
confidence: 98%
“…Modifications to the approach over the years have included the use of a quality index (Stevens, 1966), incorporation of substitute sites in both a seemingly unrelated regression model (Burt and Brewer, 1971) and a single equation model (Gum and Martin, 1975) and the travel-time debate (Wilman, 1980). Additionally, the number of zones, varying between individual and highly aggregated has been argued and the correct functional form of the regression model discussed by Strong (1983).…”
Section: Theoretical Issuesmentioning
confidence: 98%
“…patterns of locational decisions (especially housing purchases) might reveal their marginal values. Stevens (1966) hypothesized that a lake's water quality would only be a concern to those who used the lake.…”
Section: Strategies For Measuring Environmental Valuesmentioning
confidence: 99%